Pengaruh Pemasaran Media Sosial TikTok dan Duta Merek terhadap Niat Beli Melalui Citra Merek pada Produk Azarine - Florensia Gomeda Simanungkalit; Saida Zainurrosalamia Za (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Purpose of this study is to examine how influential TikTok social media marketing and brand ambassadors are on purchase intention through brand image on Azarine products. The independent variables in this study are social media marketing and brand ambassadors, the intervening variable is brand image, while the dependent variable is purchase intention. The population in this study were 128 people who are generation Z in Samarinda. The study used purposive sampling. The type of data used is quantitative data, obtained directly using a questionnaire. Data analysis using SEM-PLS 4.0, including validity, reliability, and hypothesis testing. The research results showed: 1) TikTok social media marketing has a significant and positive direct impact on brand image and purchase intention; 2) brand ambassadors have a significant and positive direct impact on brand image and purchase intention; 3) brand image has a significant and positive direct impact on purchase intention; 4) TikTok social media marketing positively and significantly affects purchase intention through brand image; 5) brand ambassadors positively and significantly influence purchase intention through brand image. Social media and brand ambassadors need to be managed properly because they can be effective tools in product marketing.